Total Hip Arthroplasty After Acetabular Fractures - Torchynskyi, V.P.; Liabakh, A.P. (TERRA ORTHOPAEDICA, 2025)
Relevance. The consequences of acetabular fractures most often manifest as coxarthtrosis and/or aseptic necrosis of the femoral head. One of the most important issues is proper positioning of the artificial hip socket, which depends on anatomical conditions.Objective. This study aims to analyze the outcomes of total hip arthroplasty (THA) in patients with sequelae of acetabular fractures and to compare functional results depending on the complexity of acetabular component positioning.Material and Methods. Seventy patients aged 24–67 years with sequelae of acetabular fractures who underwent THA were divided into two groups: group I (31 cases), when the positioning of the acetabular component was not problematic; group II (39 cases), when the positioning of the acetabular component of the prosthesis was technically difficult. Functional outcomes were assessed in all patients 2–15 years after surgery using the Harris Hip Score (HHS).Results. Baseline HHS scores were significantly higher in group I compared with group II (55.7 ± 11.7 vs. 35.9 ± 10.4; p < 0.001, two-sample t-test). Final THA outcomes were also significantly better in group I than in group II (94.3 ± 4.6 vs. 90.6 ± 8.7; p = 0.026, two-sample t-test). However, consideration of the minimal clinically important difference (MCID) for HHS indicated a clinically insignificant difference.Conclusions. Accurate restoration of anatomy, particularly the hip joint’s center of rotation, is a key success factor ensuring proper prosthesis function, stability, optimal muscle biomechanics, and implant longevity. An individualized and differentiated approach to THA in patients with sequelae of acetabular fractures allows for good and excellent anatomical and functional treatment outcomes, with the average HHS values exceeding 90 percent.